Calagem em solos de várzeas de Minas Gerais critérios de recomendação com base em parâmetros de acidez e ou propriedades químicas dos solos - Regitano, Jussara Borges (1987)
Lowland soils with potential for irrigation in Brazil occupy aproximately 30 million hectares. These soils with no defined utilization could be incorporated to the agricultural frontier, increasing the productive potential for food grains in the country. Lowland soils when flooded present physical, physical chemistry and electro-chemical changes as a function of reduced conditions, mainly increase in pH value and neutralization of exchangeable aluminum. Under these conditions there is not a positive response to lime use. However, under drainage systems that reverse these changes, these soils have shown controversial responses in terms of lime use. The lack of basic studies concerning methods to define rates of lime for lowland soils in Brazil, under drainage systems, justifies this research work which had the following objectives: a) to get fundamental informations concerning lime needs for lowland soils as a function of their buffer capacity; b) to suggest alternatives for use of conventional methods of lime recommendation for these soils. Thirty-three top-soil samples (0 to 20 cm) were taken to represent lowland soils of Minas Gerais State. These samples were air-dried, sieved through a 5mm opening sieve and submitted to incubation process. The treatments envolved seven rates of lime 0.0; 0.2;0.4; 0.6; 0.8; 1.0 and 1.5 times the rate to achieve 100% basis saturation. The experimental design was completely randomized with three replications. The samples under incubation were checked for pH in water, initially at seven days, after that at fifteen days intervals until reaching equilibrium pH (after two months of incubation). After this period, the samples were air-dried, sieved through a 2 mm opening sieve and analized in relation to the following parameters: exchangeable Ca, Mg, Al, potential acidity (H + Al), extractable K, pH in water, pH in 0.01 M CaCl2 and pH in 1.0 NKCl. This research allowed the following conclusions: - The potential acidity (H + Al) of lowland soils of Minas Gerais State can be estimated by the equilibrium pH obtained with a SMP buffered solution through the equation: H + Al = 300870,77 (pH SMP)⁻⁶’¹ - The cation exchange capacity of lowland soils of Minas Gerais State varies mainly as a function of organic matter content, being minimum the contribution of the mineral fraction. - With exception of pH in water, pH in 0.01 M CaCl2 and basis saturation, all the acidity parameters and/or chemical properties evaluated (pH SMP, Al, H + Al, organic matter, organic matter and Al, organic matter and pH in water, organic matter and pH in 0.01 M CaCl2) were efficient to predict necessary lime rates to achieve pH in water values of 5.0; 5.5; 6.0 and 6.5, and basis saturation of 40, 50, 60 and 70%. - Under practical point of view, it is suggested the use of H + Al, and organic matter and pH in water, to estimate lime rates for lowland soils. - The traditional methods of lime recommendation based upon basis saturation and exchangeable aluminum, underestimated the lime needs when compared to the incubation process. - Rates of lime based upon pH SMP to achieve pH in water values of 5.5 and 6.0, were very close to those determined by the incubation process.